2016
DOI: 10.1080/09602011.2016.1258367
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of recommended modifications of CBT for people with cognitive impairments following brain injury

Abstract: Due to diverse cognitive, emotional and interpersonal changes that can follow brain injury, psychological therapies often need to be adapted to suit the complex needs of this population. The aims of the study were to synthesise published recommendations for therapy modifications following brain injury from non-progressive traumatic, vascular, or metabolic causes and to determine how often such modifications have been applied to cognitive behavioural therapy (CBT) for post-injury emotional adjustment problems. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 62 publications
1
52
0
6
Order By: Relevance
“…One of the possible reasons for the lack of efficacy was that psychological treatments need to be tailored for people with aphasia and cognitive impairment. 22,25 A systematic review 26 of the modifications to CBT that were required for people with cognitive impairments caused by acquired brain injury reported promoting an understanding of how specific changes to cognition, affect and behaviour occur as a result of brain injury and the use of memory aids. 27 However, a randomised trial of augmented CBT, in which CBT was adapted to suit those with stroke, also found no evidence of benefit in comparison with a cognitive training control group.…”
Section: Factors Associated With Depression After Strokementioning
confidence: 99%
“…One of the possible reasons for the lack of efficacy was that psychological treatments need to be tailored for people with aphasia and cognitive impairment. 22,25 A systematic review 26 of the modifications to CBT that were required for people with cognitive impairments caused by acquired brain injury reported promoting an understanding of how specific changes to cognition, affect and behaviour occur as a result of brain injury and the use of memory aids. 27 However, a randomised trial of augmented CBT, in which CBT was adapted to suit those with stroke, also found no evidence of benefit in comparison with a cognitive training control group.…”
Section: Factors Associated With Depression After Strokementioning
confidence: 99%
“…Bei Planung und Umsetzung psychotherapeutischer Maßnahmen gilt es insbesondere auf exekutive Störungen, motivationale Probleme, Störungen der Emotionalität oder der Krankheitseinsicht, eine verminderte psychophysische Belastbarkeit und andere Beeinträchtigungen zu achten, die eine angemessene Mitarbeit behindern [98]. Das Vorliegen einer hirnorganischen Schädigung schließt eine psychotherapeutische Intervention aber nicht aus, im Gegenteil.…”
Section: Organisch Psychische Störungenunclassified
“…Garcia et al, [25] posited that recreation and the community play a role in enhancing the daily functioning of patients with schizophrenia, whereas Garrido et al, [26] stated that to improve the quality of life in patients with schizophrenia, active treatment for negative symptoms, psychological distress and resistance should be recommended. In addition, Gallagher et al, [8] have asserted in their study that since CBT includes elements of cognitive rehabilitation therapy, it is considered an effective cure alongside drug therapy in the treatment of schizophrenic patients, and can thus be applied as an effective intervention for schizophrenic patients in Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Such impairments prevent patients from developing social relationships, fulfi lling their social roles or meeting their social needs, resulting in a decrease in their quality of life [6]. Early detection and treatment is critical because, if left untreated, schizophrenia, or any form of mental illness for that matter, has significant negative consequences for academic achievement [7,8], employment [9], substance misuse [10] and social relationships [11]. In the treatment of schizophrenia, pharmacologic approaches and psychosocial interventions are supplementary of each other [12].…”
Section: Introductionmentioning
confidence: 99%